Emulating dendritic computing paradigms on analog neuromorphic hardware - Kaiser, Jakob; Billaudelle, Sebastian; Müller, Eric; Tetzlaff, Christian; Schemmel, Johannes; Schmitt, Sebastian (Neuroscience, 2022)
BrainScaleS-2 is an accelerated and highly configurable neuromorphic system with physical models of neurons and synapses. Beyond networks of spiking point neurons, it allows for the implementation of user-defined neuron morphologies. Both passive propagation of electric signals between compartments as well as dendritic spikes and plateau potentials can be emulated. In this paper, three multi-compartment neuron morphologies are chosen to demonstrate passive propagation of postsynaptic potentials, spatio-temporal coincidence detection of synaptic inputs in a dendritic branch, and the replication of the BAC burst firing mechanism found in layer 5 pyramidal neurons of the neocortex.